Effects of Obesity on Pulmonary Inflammation and Remodeling in Experimental Moderate Acute Lung Injury - Maia, Lígia de A.; Cruz, Fernanda F.; de Oliveira, Milena V.; Samary, Cynthia S.; Fernandes, Marcos Vinicius de S.; Trivelin, Stefano de A. A.; Rocha, Nazareth de N.; Gama de Abreu, Marcelo; Pelosi, Paolo; Silva, Pedro L.; Rocco, Patricia R. M. (Frontiers in Immunology, 2019)
Obese patients are at higher risk of developing acute respiratory distress syndrome (ARDS); however, their survival rates are also higher compared to those of similarly ill non-obese patients. We hypothesized that obesity would not only prevent lung inflammation, but also reduce remodeling in moderate endotoxin-induced acute lung injury (ALI). Obesity was induced by early postnatal overfeeding in Wistar rats in which the litter size was reduced to 3 pups/litter (Obese, n=18); Control animals (n=18) were obtained from unculled litters. On postnatal day 150, Control and Obese animals randomly received E. coli lipopolysaccharide (ALI) or saline (SAL) intratracheally. After 24h, echocardiography, lung function and morphometry, and biological markers in lung tissue were evaluated. Additionally, mediator expression in neutrophils and macrophages obtained from blood and bronchoalveolar lavage fluid (BALF) was analyzed. Compared to Control-SAL animals, Control-ALI rats showed no changes in echocardiographic parameters, increased lung elastance and resistance, higher monocyte phagocytic capacity, collagen fiber content, myeloperoxidase (MPO) activity, and levels of interleukin (IL-6), tumor necrosis factor (TNF)-α, transforming growth factor (TGF)-β, and type III (PCIII) and I (PCI) procollagen in lung tissue, as well as increased expressions of TNF-α and monocyte chemoattractant protein (MCP)-1 in blood and BALF neutrophils and. Monocyte (blood) and macrophage (adipose tissue) phagocytic capacities were lower in Obese-ALI compared to Control-ALI animals, and Obese animals exhibited reduced neutrophil migration compared to Control. Obese-ALI animals, compared to Obese-SAL, exhibited increased interventricular septum thickness (p=0.003) and posterior wall thickness (p=0.003) and decreased pulmonary acceleration time to pulmonary ejection time ratio (p=0.005); no changes in lung mechanics, IL-6, TNF-α, TGF-β, PCIII and PCI in lung tissue; increased IL-10 levels in lung homogenate (p=0.007); reduced MCP-1 expression in blood neutrophils (p=0.009); decreased TNF-α expression in blood (p=0.02) and BALF (p=0.008) neutrophils; and increased IL-10 expression in monocytes (p=0.004). In conclusion, after endotoxin challenge, obese rats showed less deterioration of lung function, secondary to anti-inflammatory and antifibrotic effects, as well as changes in neutrophil and monocyte/macrophage phenotype in blood and BALF compared to Control rats.